Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299